Impact of Online and Social Media Platforms in Organizing the Events: A Case Study on Coke Fest and Pakistan Super League. - Haider, S. A.; Rehman, F.; Tehseen, Shehnaz * (Routledge. Taylor and Francis, 2022)
Organizing events on an online platform seems to be a challenging task. Due to the COVID-19 pandemic, many companies all over the world have catered to an online system of ticketing for major events and use social media as a platform to create awareness and promote themselves. However, in the developing country Pakistan e-ticketing, promoting websites, mobile applications and social media is a new phenomenon. Most tickets for events are sold the traditional way and the shift to e-ticketing can be a tricky business. The purpose of this study is to investigate how information and communications technologies (ICT) factors influence major events, namely Coke Fest 2020 and Pakistan Super League (PSL) in the year 2019 and 2020. The Coke Fest is a music-food amalgamation that brings the two passions of Pakistanis in one place, the Coca-Cola Food and Music Festival. However, PSL is a professional Twenty20 cricket league contested and has become the second most expensive cricket league in Asia. Both events attract millions of people all across Pakistan and have a huge fan following worldwide. The hypotheses were supported through secondary sources such as journal articles, newspaper articles, newspaper columns, press releases, government sources along with recent research on COVID-19. Finally, some theoretical and practical contributions to ICT literature as well as research limitations and future directions were presented.